The Effectiveness of Picture Series as a Media to Improve Students' Writing Skill - Wahyu Ilmillahdini, Yayi; Sumarsono, Puji (Celtic: A Journal of Culture, English Language Teaching, Literature and Linguistics, 2014)
The Effectiveness of Picture Series as a Media to Improve Students' Writing Skill